2020
DOI: 10.3390/agronomy10121856
|View full text |Cite
|
Sign up to set email alerts
|

Is Drought Stress Tolerance Affected by Biotypes and Seed Size in the Emerging Oilseed Crop Camelina?

Abstract: One of the main advantages of camelina (Camelina sativa (L.) Crantz) is its wide environmental adaptability and extreme drought tolerance. The availability of both winter and spring camelina biotypes, characterized by different seed sizes, raises the question about possible differences in their response to drought stress at the emergence stage. To address this, a germination test was set up in controlled conditions, comparing six winter and six spring genotypes with differing seed sizes (ranging from 1.83 to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The confirmed superiority of camelina compared with oilseed rape as well as Brassica carinata and B. juncea, means that it is much more resilient to environmental stresses, which leads to its higher performance under rain-fed conditions [47]. Camelina seed yield and quality widely varied across the DH lines in the present study during two cropping seasons.…”
Section: Discussionsupporting
confidence: 63%
“…The confirmed superiority of camelina compared with oilseed rape as well as Brassica carinata and B. juncea, means that it is much more resilient to environmental stresses, which leads to its higher performance under rain-fed conditions [47]. Camelina seed yield and quality widely varied across the DH lines in the present study during two cropping seasons.…”
Section: Discussionsupporting
confidence: 63%
“…In particular, results confirmed that Joelle seed is characterized by relatively small size, as in the study by Wittenberg et al (2020), who found that the TKW ranged from 0.96-1.28 g across different years and sowing dates in the US Great Plains. However, winter camelina varieties with larger seed size are available, like Bison, but when compared with Joelle, it showed lower winter survival (Gesch et al, 2018), and a study by Canak et al (2020) indicates that Bison may be more susceptible to drought during germination and emergence. The seed weight of Joelle in the present study increased when precipitation was more evenly distributed throughout the crop's growth cycle, including the 50% flowering to harvest period (Table 4), confirming that camelina is susceptible to heavy moisture conditions causing a general decrease in its qualitative performance (Gesch and Cermak, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Calena exhibited germination up to 150 mM NaCl and thus might be suitable for cultivation in saline soils [ 293 ], but additional research is required to confirm this suggestion. Comparison of two different genotypes of C. sativa showed that increased water-deficit stress tolerance was associated with differences in stomatal conductance and increased accumulation of osmoprotectants such as proline, sugars, amino acids, and soluble proteins [ 294 ]. Screening of winter and spring genotypes revealed differences in germination under artificial osmotic stress imposed by different concentrations of polyethylene glycol (PEG) [ 295 ].…”
Section: Strategic Innovations For Climate-resilient C Sativamentioning
confidence: 99%